437 Effects on presenteeism owing to fear-avoidance beliefs of workers with musculoskeletal pain: a one-year cohort study. (24th April 2018) - Ikegami, K; Sugano, R; Michii, S; Ando, H; Nozawa, H; Shirasaka, T; Kondo, M; Imoto, H; Shima, A; Kawatsu, Y; Ogami, A
Abstract : Introduction: Previous studies have reported on the relationship between workers' presenteeism, specifically where a loss of work productivity results from an employee's health problems, and musculoskeletal pain (MSP). Other studies have reported that chronicity and an increase in lower back pain were brought on by individual fear–avoidance beliefs. We considered that workers' fear-avoidance beliefs linked with MSP cause chronic MSP and exacerbate their presenteeism. The aim of this study was to clarify the effects of presenteeism arising from fear–avoidance beliefs among workers with MSP. Methods: We conducted a prospective study issuing self-administered questionnaires to 3406 workers in 118 companies, from June 2016 to February 2017. We distributed questionnaires on two occasions and obtained responses from 1673 individuals (response rate: 49.1%). In total, 1490 individuals were eligible for this survey (effective response rate: 89.1%). We excluded individuals whose pain status responses were not clear. We sought information from participants about various individual and work-related characteristics and the prevalence of MSP using an original questionnaire. The Work Functioning Impairment Scale (Wfun) was used to measure presenteeism, and the Tampa Scale for Kinesiophobia (TSK) was used to measure fear–avoidance beliefs. We statistically analysed the change in the Wfun and the TSK scores among groups with: no prevalence of MSP; transitional MSP (in two groups, with participants either developing or recovering from MSP), and; chronic MSP. Results: The Wfun score in the chronic MSP group was significantly higher than that of the other groups for both survey measures. The TSK score of the chronic MSP group was also significantly higher than for the transitional MSP groups. We observed a significant positive correlation between the change of Wfun score and TSK score. Conclusion: Our study suggests that fear-avoidance beliefs of workers with MSP leads to MSP chronicity, and exacerbates worker presenteeism.